Human chorionic gonadotropin stimulation gives evidence of differences in testicular steroidogenesis in Klinefelter syndrome, as assessed by liquid chromatography–tandem mass spectrometry. Issue 6 (June 2016) - Belli, S; Santi, D; Leoni, E; Dall'Olio, E; Fanelli, F; Mezzullo, M; Pelusi, C; Roli, L; Tagliavini, S; Trenti, T; Granata, A R; Pagotto, U; et al.
Abstract : Background: Men with Klinefelter syndrome (KS) show hypergonadotropic hypogonadism, but the pathogenesis of hypotestosteronemia remains unclear. Testicular steroidogenesis in KS men was evaluated over three decades ago after human chorionic gonadotropin (hCG) stimulation, but inconclusive results were obtained. Intriguingly, some recent studies show increased intratesticular testosterone concentrations in men with KS. Objective: To analyze serum steroid profile, as a proxy of testicular steroidogenesis, after hCG stimulation in KS compared with control men. Design: A prospective, longitudinal, case–control, clinical trial. Methods: Thirteen KS patients (36±9 years) not receiving testosterone (TS) replacement therapy and 12 eugonadic controls (32±8 years) were enrolled. Serum steroids were measured by liquid chromatography–tandem mass spectrometry (LC–MS/MS) at baseline and for five consecutive days after intramuscular injection of 5000IU hCG. Results: Progesterone (P), 17-hydroxyprogesterone (17OHP), TS, and estradiol (E2) showed a significant increase ( P <0.001) after hCG stimulation in both groups. On the contrary, androstenedione (AS) and dehydroepiandrosterone did not increase after hCG stimulation. The 17OHP/P ratio increased in both groups ( P <0.001), the TS/AS ratio (17β-hydroxysteroid dehydrogenase type 3 (17βHSD3) activity) did not increase after hCG in any group, and the E2/TS ratio (aromatase activity) increased significantly in both groups ( P =0.009 in KS and P <0.001 in controls). Luteinizing hormone decreased after hCG in both groups ( P =0.014 in KS and P <0.001 in controls), whereas follicle-stimulating hormone decreased only in control men ( P <0.001). Conclusion: This study demonstrates for the first time using LC–MS/MS that Leydig cells of KS men are able to respond to hCG stimulation and that the first steps of steroidogenesis are fully functional. However, the TS production in KS men is impaired, possibly related to reduced hydroxysteroid deydrogenase activity due to an unfavorable intratesticular metabolic state.